1992
DOI: 10.1002/sia.740180111
|View full text |Cite
|
Sign up to set email alerts
|

Probing depth of soft x‐ray absorption spectroscopy measured in total‐electron‐yield mode

Abstract: Two series of experiments on wellcharacterized systems were performed to examine the probing depth of soft x-ray absorption spectroscopy (XAS) measured in total-electron-yield (TEY) mode. First we measured the Ni 2p,,, absorption spectra of Ni(100) covered with Tb as a function of the overlayer thickness. Secondly we recorded the 0 Is absorption spectra of Ta,O, films produced by controlled anodic oxidation of Ta foils as a function of the oxide thickness. The mean probing depth (MPD) was found to be much shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(141 citation statements)
references
References 19 publications
4
133
1
Order By: Relevance
“…similar to the largest probing depth in our experiments. [37] It is also noteworthy that in the case of CH 3 OH:O 2 =3:1 the O:Cu stoichiometry close to the surface is similar to that of Cu 2 O. The valence band spectra in Fig.…”
Section: Resultsmentioning
confidence: 67%
“…similar to the largest probing depth in our experiments. [37] It is also noteworthy that in the case of CH 3 OH:O 2 =3:1 the O:Cu stoichiometry close to the surface is similar to that of Cu 2 O. The valence band spectra in Fig.…”
Section: Resultsmentioning
confidence: 67%
“…19 One detector measures the gas phase, while a second detector (close to the sample surface) detects both the gas phase and surface signal, where "surface" is defined here as the top 4 nm of the sample. The surface signal can be revealed through subtraction of the gas-phase signal.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, except for the few materials for which the sampling depth has been experimentally determined, the depth sensitivity of this technique is still under discussion. Previous studies on transition metals and rare earths showed a strong dependence of d on the investigated material, in the range 1.5 -2.5 nm for metallic Fe, Ni, Co, Dy and Tb for photon energies in the range 700 -900 eV [4,5,6,7,8,9]. Because of the different electronic structure between metals and insulators, in particular the gap in the density of states near the Fermi level in the latter that will influence the secondary electron cascade, insulators are expected to have a larger electron sampling depth.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the different electronic structure between metals and insulators, in particular the gap in the density of states near the Fermi level in the latter that will influence the secondary electron cascade, insulators are expected to have a larger electron sampling depth. Little literature is available on this topic [9,10,11,12]. Gota et al [11] found an unexpectedly high value for the sampling depth of the iron magnetic oxide Fe 3 O 4 of 4.5 nm, in comparison to the one known for metallic Fe in the range 1.7 -2.2 nm, while d ≈ 2nm was found both in Ta 2 O 5 at the O K-3 edge [9] and in LaFeO 3 at the Fe L 2,3 edge [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation